Lung autotransplantation combined with postoperative chemotherapy and immunotherapy: a three-year follow-up case report - Jiang Wang; Tong Li; Hengxiao Lu; Qiang Zhao (World Journal of Surgical Oncology)
Abstract Background Lung cancer remains a leading cause of cancer-related mortality worldwide. Autotransplantation has emerged as a potential surgical intervention in select cases, with the aim of achieving curative outcomes. This case report describes a novel approach combining lung autotransplantation with postoperative chemotherapy and immunotherapy, delineating the patient's journey over a period of three years. Case presentation We report on a 37-year-old patient with stage IIIA non-small cell lung cancer (NSCLC) who underwent lung autotransplantation. Despite the complexity of the procedure, the patient had a favorable postoperative course. Adjuvant therapy included a PD-1 inhibitor and a standard chemotherapy regimen. The patient’s follow-up involved regular clinical assessment, imaging, and functional status evaluation, demonstrating a remarkable disease-free survival at the three-year mark postoperatively. Conclusion This case highlights the potential for lung autotransplantation coupled with immunotherapy and chemotherapy to yield significant long-term survival benefits in patients with NSCLC. The favorable outcome suggests that this integrative treatment strategy warrants further investigation and may offer hope to patients with similarly advanced lung cancer.